Geomorfologi Daerah Bolihutuo dan Sekitarnya, Kecamatan Botumoito, Provinsi Gorontalo - Paendre, Asdini; Arifin, Yayu Indriati; Raharjo, Purnomo (Universitas Negeri Gorontalo, 2025)
The Bolihutuo area and its surroundings, in the Botumoito District, have geomorphological characteristics that are interesting for research, as they feature complex geomorphological conditions influenced by volcanic activity, fluvial processes, and structural factors. This study aims to map and classify the geomorphological units in the research area. The methods applied include spatial analysis and field observation. The results of this study indicate that the area has four main geomorphological units: structural hill units, volcanic hill units, fluvial plain units, and marine plain units. The morphography of the research area consists of lowlands and low hills with elevations ranging from 0 to 187.5 meters above sea level. Slope gradients vary from flat to very steep, while the river flow patterns are sub-parallel with young and mature river stages.The lithology consists of gabbro, andesite, granodiorite, granite, dacite, and alluvial deposits, and the land can be utilized for settlements, agriculture, and infrastructure development, adjusted according to its slope.